2003
DOI: 10.1074/jbc.m302766200
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-anchoring and Charge Effects in the Interaction of Myelin Basic Protein with Lipid Bilayers Studied by Site-directed Spin Labeling

Abstract: Myelin basic protein (MBP) maintains the compaction of the myelin sheath in the central nervous system by anchoring the cytoplasmic face of the two apposing bilayers and may also play a role in signal transduction. Site-directed spin labeling was done at eight matching sites in each of two recombinant murine MBPs, qC1 (charge ؉19) and qC8 charge (؉13), which, respectively, emulate the native form of the protein (C1) and a posttranslationally modified form (C8) that is increased in multiple sclerosis. When inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
112
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 80 publications
(123 citation statements)
references
References 53 publications
8
112
0
Order By: Relevance
“…The calibration of the ⌽ value with the depth of penetration was especially important for the Cyt-LUVs, because they consisted of six different lipid components, including 40% cholesterol. The effect of the cholesterol was to increase the penetration of NiEDDA up to the fifth carbon of the acyl group of the phospholipid, as reported previously (22). The hyperbolic tangent function (Eq.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The calibration of the ⌽ value with the depth of penetration was especially important for the Cyt-LUVs, because they consisted of six different lipid components, including 40% cholesterol. The effect of the cholesterol was to increase the penetration of NiEDDA up to the fifth carbon of the acyl group of the phospholipid, as reported previously (22). The hyperbolic tangent function (Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of Large Unilamellar Vesicles (LUVs)-Aliquots of the chloroform solutions of various lipids were combined in the following molar ratios to form large unilamellar vesicles (LUVs) with a lipid composition similar to that estimated for the cytoplasmic face of the myelin membrane (Cyt-LUVs): 44 mol % cholesterol, 27 mol % PE, 13 mol % phosphatidylserine, 11 mol % PC, 3 mol % sphingomyelin, and 2 mol % PI (22). The solvent was evaporated under a stream of nitrogen, dried in a vacuum desiccator overnight, and then hydrated in 20 mM HEPES-NaOH, pH 7.4, and 10 mM NaCl.…”
Section: Site-directed Mutagenesis Protein Expression and Purificatmentioning
confidence: 99%
See 2 more Smart Citations
“…Far less is known regarding the role of aspartic proteases, cathepsins D and E, in MS. Cathepsin D degrades myelin basic protein (MBP) [15,291], and at least one study has shown that pepstain, an inhibitor of cathepsin D, suppresses clinical and histological signs of EAE [29]. Of interest, cathepsin D was among the genes upregulated by more than 2.5-fold in a large-scale cDNA sequencing study of MS plaques [39].…”
Section: Threonine and Aspartic Proteasesmentioning
confidence: 99%